Field and laboratory evaluation of DGT for predicting metal bioaccumulation and toxicity in the freshwater bivalve Hyridella australis exposed to contaminated sediments. (December 2018) - Amato, Elvio D.; Marasinghe Wadige, Chamani P.M.; Taylor, Anne M.; Maher, William A.; Simpson, Stuart L.; Jolley, Dianne F.
Abstract: The diffusive gradients in thin films (DGT) technique has shown to be a useful tool for predicting metal bioavailability and toxicity in sediments, however, links between DGT measurements and biological responses have often relied on laboratory-based exposures and further field evaluations are required. In this study, DGT probes were deployed in metal-contaminated (Cd, Pb, Zn) sediments to evaluate relationships between bioaccumulation by the freshwater bivalve Hyridella australis and DGT-metal fluxes under both laboratory and field conditions. The DGT-metal flux measured across the sediment/water interface (±1 cm) was useful for predicting significant cadmium and zinc bioaccumulation, irrespective of the type of sediment and exposure. A greater DGT-Zn flux measured in the field was consistent with significantly higher zinc bioaccumulation, highlighting the importance of performing metal bioavailability assessments in situ . In addition, DGT fluxes were useful for predicting the potential risk of sub-lethal toxicity (i.e., lipid peroxidation and lysosomal membrane damage). Due to its ability to account for multiple metal exposures, DGT better predicted bioaccumulation and toxicity than particulate metal concentrations in sediments. These results provide further evidence supporting the applicability of the DGT technique as a monitoring tool for sediment quality assessment. Graphical abstract: Image 1 Highlights: Laboratory and field sediment bioassays provided different predictions of risk. The exposure of organisms to metals differed between laboratory and field bioassays. DGT predicted the risk of bioaccumulation and toxicity irrespective of the exposure. In situ evaluation of metal bioavailability may improve sediment quality assessment. Abstract : DGT was useful for predicting bioaccumulation and sublethal toxicity to organisms exposed to metal contaminated sediments irrespective of type of sediment and exposure.